Avaliação do perfil fitoquímico, toxicidade e comportamento do extrato das folhas de Morus nigra Linnaeus frente à sobrecarga de ferro - Figueredo, Kássia Caroline (2017)
Morus nigra is a plant popularly known as "amoreira preta". It is used in folk medicine to soften the effects of menopause, such as anti-inflammatory, antidiabetic and antihypertensive. However, information on safe doses and use is still precarious. Iron overload is a clinical condition that causes damage to the liver tissue due to oxidative stress. Therapy to control iron overload is still unsatisfactory. The objective of the study was to perform a phytochemical, toxicological and evaluation of the effect on iron overload of the extract of the leaves of M. nigra (EEMN). The chromatographic profile revealed caffeic acid and quercetin as major compounds in the EEMN. In the acute toxicological study (2000 mg/kg) and subacute, the extract was administered by oral gavage. For subacute, EEMN was tested in male and female rats at doses of 500, 750 and 1000 mg/kg for 28 days. Behavioral changes, object recognition test, renal and hepatic tissue assessments, biochemical, and hematological were determined. In the acute treatment the EEMN was classified as safe. In the sub-acute study, there was a decrease in AST in males (750 and 1000 mg/kg) and females (1000 mg/kg), reduction of total cholesterol in females (750 and 1000 mg/kg), increase in renal and hepatic change the LPO levels. The EEMN presented potentially protective action of organs and supposed hypocholesterolemic activity. For evaluation of iron overload, male Wistar rats were divided into 6 groups. To induce iron overload, the induced groups received iron dextran (50 mg/kg/day) and not overloaded received 0.9% saline intraperitoneal (i.p.). To test treatment, ethanol 53% was used as vehicle. The groups were divided as follows: I (CG): Control group (ethanol 53% - 10 mL/kg); II (IOV): Iron overload + vehicle (ethanol 53% - 10 mL/kg); III (NO500): Non-overload + EEMN 500 mg/kg (10 mL/kg); IV (IO500): Iron overload + EEMN 500 mg/kg (10 mL/kg); V (IO1000): Iron overload + EEMN 1000 mg/kg (10 mL/kg); VI (DFO): Iron overload + DFO (10 mg/kg/day). The vehicle and EEMN were administered by oral gavage, DFO was administered via i.p. They were analyzed body weight, hepatosomatic index (HSI), serum iron, hepatic markers, cytokines, interfering factors in iron metabolism, enzymatic and histopathological evaluations. The experimental model showed increased levels of serum iron, hepcidin, ALT and proinflammatory cytokines (IOV), histopathology showed that iron overload causes damage to the liver tissue. Our findings illustrate a new therapeutic action and economically viable ff the leaves of M. nigra in hepatic iron overload, however the compounds in the plant responsible for the pharmacological action still need to be elucidated.